Resolution of hypogammaglobulinemia-associated recurrent Campylobacter bacteraemia after hematopoietic cell transplantation (HCT) - Emmanouil Karofylakis, MD; Effrossyni Gkrania-Klotsas, MD, MPH, FRCP, PhD; Benjamin Uttenthal, MA, MBBS, PhD, MRCP, FRCPath; Dinakantha Kumararatne, MBBS, FRCPath, DPhil (Journal of Allergy and Clinical Immunology: Global)
Primary or secondary hypogammaglobulinemia is associated with persistent norovirus and Campylobacter infections despite immunoglobulin replacement therapy. Allogeneic hematopoietic cell transplantation for hematologic indications can lead to immune reconstitution by correcting a previously undiagnosed concurrent primary immunodeficiency.